Teaching English for Academic Purposes in the KU Academic Accelerator Program - Berardo, Marcellino; Smith Herrod, Kellie (Issues in Language Instruction, 2018)
The Kansas University Academic Accelerator Program (KUAAP) is new to the University and brings with it a reconceptualization of the first year experience for newly arrived international students who have not yet fulfilled the University’s English as a second language requirements. In their first two terms, international students in KUAAP take classes in English for academic purposes (EAP) alongside General Education (Gen Ed) courses. By their third term, students no longer take EAP classes.